(untitled) - Lạc, Minh Thư (Cần Thơ, 2018)
The present study is aimed to shed light on the effects of cognitive reading strategy training on EFL students’ reading performance in an upper secondary school in Vietnam. Also, this study aims to find out the students’ perception about the training for using cognitive reading strategies after a short period of training. The author was really motivated to choose this topic based on the belief that reading is an indispensable language skill for EFL students but reading nervousness – a common issue in the process of learning English – was reported to prevent learners from acquiring foreign language.
Keywords: Tiếng Anh,English language; Học và dạy học,Study and teaching